toner
Patent Information
- Application Number
- JP2021032708
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-03-02
AI Technical Summary
【0006】 本開示によれば、定着画像表面の離型性向上と共に、厚紙における定着画像の耐折り曲げ性が良化したトナーを提供することができる。
Smart Images

Figure 0007631032000014 
Figure 0007631032000001 
Figure 0007631032000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to toners for developing electrostatic images used in electrophotography, electrostatic recording, and the like. [Background technology]
[0002] In recent years, full-color electrophotographic copiers have become widespread and are beginning to be applied to the printing market. In the printing market, there is a growing demand for high speed, high image quality, and high productivity while being compatible with a wide range of media (paper types). For example, even when the paper type is changed from thick paper to thin paper, there is a demand for media uniformity, which means that printing can continue without changing the process speed to match the paper type or the heating temperature setting of the fixing unit. Toner is required to be able to be fixed properly in a wide range of temperatures from low to high in order to meet the media uniformity. On the one hand, toner is required to be softened at low temperatures, but on the other hand, it is necessary to suppress toner offset caused by increased adhesion to the fixing member at high temperatures and sticking of paper to the fixing member. In the printing market, printed matter is used for a wide range of purposes. For package printing and printing on cardboard, images must be durable enough to withstand bending without being damaged. Patent Document 1 discloses a toner that uses a polyester resin grafted with silicone oil to improve the releasability of a fixed image and suppress toner offset and sticking of paper to members. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 08-087127 Summary of the Invention [Problem to be solved by the invention]
[0004] The toner in the above-mentioned document uses a polyester resin grafted with silicone oil as an additive in order to improve the releasability of the fixed image surface, and the silicone part reduces the intermolecular cohesive force inside the toner particles. Therefore, it was found that there is room for improvement in the folding resistance of the fixed image. The present disclosure provides a toner that improves the releasability of the surface of a fixed image and improves the folding resistance of a fixed image on thick paper. [Means for solving the problem]
[0005] The present disclosure relates to a toner having toner particles containing a binder resin, The binder resin contains 50% by mass or more of a polyester resin, The polyester resin contains a polyester resin A having a structure represented by the following formula (1): In an analysis of the toner particles using an X-ray photoelectron spectrometer, it was found that the -(Si(R X )2O) n -Si(R X )2-, the ratio of the number of silicon atoms belonging to the silicone moiety to the total number of atoms measured (number of silicon atoms / total number of atoms×100) is defined as X, the value of X on the surface of the toner particle is defined as X1, and the value of X at a position 30 nm deep from the surface of the toner particle is defined as X2, In an analysis of the toner particles using an X-ray photoelectron spectrometer, the ratio of the number of carbon atoms attributable to the ester bond of the polyester resin to the total number of atoms measured (number of carbon atoms / total number of atoms × 100) is Z, the value of Z on the surface of the toner particle is Z1, and the value of Z at a position 30 nm deep from the surface of the toner particle is Z2, X1 is 0.5 atomic % or more and 20.0 atomic % or less, A toner in which Y1 represented by the following formula (2) and Y2 represented by the following formula (3) satisfy the following formula (4). TIFF0007631032000001.tif31170 In formula (1), R Xeach independently represents a hydrogen atom, a methyl group, or a phenyl group; A represents a polyester moiety; B is a polyester moiety or -R 20 OH, -R 20 COOH, TIFF0007631032000002.tif17170, and -R 20 R represents any functional group selected from the group consisting of 20 represents a single bond or an alkylene group having 1 to 4 carbon atoms, The average number of repetitions n is 10-80. Y1=X1 / Z1 (2) Y2=X2 / Z2 (3) (Y1-Y2) / Y1≧0.50 (4) Effect of the Invention
[0006] According to the present disclosure, it is possible to provide a toner that improves the releasability of the surface of a fixed image and improves the folding resistance of a fixed image on thick paper. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a diagram showing an example of a toner surface treatment device; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The expressions "XX to YY" or "XX to YY" indicating a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified. The crystalline resin refers to a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement.
[0009] The present inventors have conducted extensive research with the aim of improving the release properties of the fixed image surface and further improving the folding resistance of the fixed image. As a result, they have found that, in a toner containing polyester resin A having a structure represented by the following formula (1), by providing a gradient in the amount of silicone moieties from the toner surface to the inside, it is possible to obtain excellent image surface release properties and folding resistance that have not been achieved in the past. [ka]
[0010] In formula (1), R X each independently represents a hydrogen atom, a methyl group, or a phenyl group; A represents a polyester moiety; B is a polyester moiety or -R 20 OH, -R 20 COOH, TIFF0007631032000004.tif17170, and -R 20 R represents any functional group selected from the group consisting of 20 represents a single bond or an alkylene group having 1 to 4 carbon atoms, The average number of repetitions n is 10 to 80 (preferably 30 to 60). R X However, each of them is preferably a methyl group.
[0011] In the structure represented by formula (1), -(Si(R X )2O) n -Si(R X The moiety represented by the formula (1) is also referred to as a silicone moiety. The present inventors consider the reason why the above effects were obtained as follows. The polyester resin A having the structure represented by formula (1) is a resin in which a polyester moiety having high polarity and a silicone moiety having low polarity are bonded (for example, covalently bonded). The polyester resin A having the structure represented by formula (1) has a silicone moiety with low polarity, which effectively reduces the surface free energy of the binder resin and improves the releasability of the image surface. However, the inventors have found that when a resin having a silicone moiety is used, the folding resistance of the fixed image, especially on thick paper, decreases. This is thought to be because the presence of the silicone moiety reduces the intermolecular cohesive force inside the toner.
[0012] Therefore, by providing a gradient in the amount of silicone moieties so that the amount of silicone moieties decreases from the surface to the interior of the toner, it is believed that it is possible to suppress a decrease in the intermolecular cohesive force inside the toner while maintaining a low surface free energy state due to the silicone moieties near the toner surface.
[0013] In the analysis of toner particles using an X-ray photoelectron spectroscopy (XPS), it was found that the silicone moiety (-(Si(R X )2O) n -Si(R X When the ratio of the number of silicon atoms belonging to the moiety represented by 2- to the total number of atoms measured (number of silicon atoms / total number of atoms×100) is X, the value X1 of X on the surface of the toner particles is 0.5 atomic % or more and 20.0 atomic % or less. X is a value that reflects the amount of silicone moieties present, and is a value that serves as an index of the amount of silicone moieties present. When X1 is within the above range, it becomes easier to control the ratio Y1 (i.e., X1 / Z1) described later within a suitable range, making it possible to achieve both releasability on the image surface and folding resistance due to the internal cohesive force inside the toner. X1 on the toner particle surface is preferably from 4.0 atom % to 15.0 atom % and more preferably from 7.0 atom % to 12.0 atom %.
[0014] Furthermore, in an analysis of toner particles using XPS, when the value of X at a position 30 nm deep from the surface of the toner particle is X2, the ratio of the number of carbon atoms belonging to ester bonds in the polyester resin to the measured total number of atoms (number of carbon atoms / total number of atoms × 100) is Z, the value of Z at the surface of the toner particle is Z1, and the value of Z at a position 30 nm deep from the surface of the toner particle is Z2, Y1 represented by the following formula (2) and Y2 represented by the following formula (3) satisfy the following formula (4): Y1=X1 / Z1 (2) Y2=X2 / Z2 (3) (Y1-Y2) / Y1≧0.50 (4) Satisfying the above formula (4) means that there is a gradient in which the amount X of silicone moieties decreases from the surface to the inside of the toner particle. It is believed that by providing such a gradient, it is possible to suppress a decrease in the intermolecular cohesive force inside the toner particle, while maintaining a low surface free energy state due to the silicone moieties in the vicinity of the toner particle surface. The steeper this gradient is, the more preferable, and the gradient is expressed numerically as the reduction rate of the ratio Y inside the toner particle relative to the toner particle surface. The value of the ratio Y in the depth direction of the toner particle can be controlled by the conditions of the heat treatment of the toner particle described later and the affinity between the silicone portion and the polyester portion.
[0015] That is, compared with the ratio Y1 on the toner particle surface, the ratio Y2 at a depth of 30 nm from the surface of the toner particle is reduced by 50% or more (preferably 50% to 95%, more preferably 55% to 80%).
[0016] In addition, when the value of X at a position 20 nm deep from the surface of the toner particle is X3 and the value of Z at a position 20 nm deep from the surface of the toner particle is Z3, it is preferable that Y3 represented by X3 / Z3 and Y1 satisfy (Y1-Y3) / Y1≧0.50. That is, it is preferable that the value of the ratio Y3 at a depth of 20 nm from the surface of the toner particle is reduced by 50% or more (preferably 50% to 95%, more preferably 55% to 80%) compared with the ratio Y1 at the surface of the toner particle. In this case, it is necessary that the reduction rate of the ratio Y is 50% or more even at a depth of 20 nm to 30 nm from the surface of the toner particle.
[0017] Furthermore, when the value of X at a position 10 nm deep from the surface of the toner particle is X4 and the value of Z at a position 10 nm deep from the surface of the toner particle is Z4, it is preferable that Y4 represented by X4 / Z4 and Y1 satisfy (Y1-Y4) / Y1≧0.50. That is, it is more preferable that the value of the ratio Y4 at a depth of 10 nm from the surface of the toner particle is reduced by 50% or more (preferably 50% to 95%, more preferably 55% to 80%) compared with the ratio Y1 at the surface of the toner particle. In this case, it is necessary that the reduction rate of the ratio Y is 50% or more even at a depth of 10 nm to 30 nm from the surface of the toner particle. It is preferred that the ratio Y decreases towards the inside of the toner particle.
[0018] The toner has toner particles containing a binder resin. The binder resin will now be described. The binder resin contains 50% by mass or more of a polyester resin. The polyester resin contains a polyester resin A having a structure represented by formula (1). In addition to the polyester resin A having a structure represented by formula (1), the binder resin may contain other resins. Examples of other resins include polyester resins, vinyl resins, polyurethane resins, epoxy resins, and phenolic resins, as well as hybrid resins in which two or more of these resins are bonded together.
[0019] In the binder resin, the content of the polyester resin including the polyester resin A having the structure represented by formula (1) is preferably 50% by mass or more. The content is preferably 70% by mass or more, more preferably 80% by mass or more. There is no particular upper limit, but it is preferably 100% by mass or less. It is particularly preferable that the binder resin is a polyester resin. By using a polyester resin as the main component of the binder resin, it is possible to effectively exert the intermolecular cohesive force inside the toner particles, and it is possible to obtain a fixed image with bending resistance. In the polyester resin, the content of polyester resin A having a structure represented by formula (1) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and even more preferably 90% by mass or more. The upper limit is not particularly limited, but is preferably 100% by mass or less. It is particularly preferable that the polyester resin is polyester resin A having a structure represented by formula (1).
[0020] The polyester resin A having the structure represented by formula (1) is -(Si(R X )2O) n -Si(R X )2-. That is, polyester resin A having a structure represented by formula (1) has a silicone moiety represented by the following formula (1'). [ka]
[0021] In formula (1´), R X and n are the same as in formula (1). X each independently represents a hydrogen atom, a methyl group, or a phenyl group. n is the average number of repetitions of the siloxane unit and represents an integer of 10 to 80 (preferably 20 to 65). In formulas (1) and (1'), R X However, each of them is preferably a methyl group.
[0022] The polyester resin A having the structure represented by formula (1) has a silicone moiety and a polyester moiety represented by formula (1'). The polyester moiety of the polyester resin A having the structure represented by formula (1) is preferably an amorphous polyester resin moiety. The components constituting the polyester moiety of the polyester resin A having the structure represented by formula (1) will be described in detail below. The following components can be used singly or in combination depending on the type and application. Examples of the divalent carboxylic acid component constituting the polyester moiety include the following dicarboxylic acids or derivatives thereof. Benzenedicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and phthalic anhydride, or their anhydrides or lower alkyl esters; alkyldicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, or their anhydrides or lower alkyl esters; alkenylsuccinic acids or alkylsuccinic acids having an average carbon number of 1 to 50, or their anhydrides or lower alkyl esters; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, and itaconic acid, or their anhydrides or lower alkyl esters.
[0023] On the other hand, examples of the dihydric alcohol component constituting the polyester moiety include the following. Ethylene glycol, polyethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-methyl-1,3-propanediol, 2-ethyl-1,3-hexanediol, 1,4-cyclohexanedimethanol (CHDM), hydrogenated bisphenol A, bisphenol and its derivatives represented by formula (I-1): and diols represented by formula (I-2). [ka]
[0024] (In the formula, R is an ethylene or propylene group, x and y are each an integer of 0 or more, and the average value of x+y is 0 or more and 10 or less.) [ka]
[0025] (In the formula, R' is an ethylene or propylene group, x' and y' are each an integer of 0 or more, and the average value of x'+y' is 0 or more and 10 or less.)
[0026] The components constituting the polyester segment may contain, in addition to the above-mentioned divalent carboxylic acid component and divalent alcohol component, a trivalent or higher carboxylic acid component and a trivalent or higher alcohol component. The trivalent or higher carboxylic acid component is not particularly limited, but examples thereof include trimellitic acid, trimellitic anhydride, pyromellitic acid, etc. Furthermore, the trivalent or higher alcohol component includes trimethylolpropane, pentaerythritol, glycerin, etc. The polyester moiety may contain, in addition to the above-mentioned compounds, a monovalent carboxylic acid component and a monovalent alcohol component as constituents.Specific examples of the monovalent carboxylic acid component include palmitic acid, stearic acid, arachidic acid, behenic acid, cerotic acid, heptacosanoic acid, montanic acid, melissic acid, lactoseric acid, tetracontanoic acid, and pentacontanoic acid. Examples of the monohydric alcohol component include behenyl alcohol, ceryl alcohol, melissyl alcohol, and tetracontanol. The content of the polyester moiety in the polyester resin A having the structure represented by formula (1) is preferably from 90.0% by mass to 99.5% by mass, and more preferably from 95.0% by mass to 98.0% by mass.
[0027] The components constituting the silicone moiety of polyester resin A having the structure represented by formula (1) are described in detail below. The following components can be used singly or in combination depending on the type and application. The silicone moiety is a structure represented by the formula (1') (-(Si(R X )2O) n -Si(R X )2-). As a component that forms a silicone moiety in polyester resin A having a structure represented by formula (1), a silicone oil having a functional group at the end of formula (1') that chemically reacts with polyester can be used. Examples of functional groups that react with polyester include hydroxyl groups, carboxyl groups, epoxy groups, and amino groups.
[0028] The functional group at the end of the silicone oil is preferably a hydroxy group or a carboxy group in order to control the reactivity with polyester. The valence of the functional group of the silicone oil is preferably 1, 2, or 3 or more. It is preferable to use a divalent silicone oil having functional groups at both ends of the silicone oil. More preferably, it is a silicone oil having a substituent containing a hydroxyl group at both ends of the formula (1'). The substituent containing a hydroxyl group is, for example, -(CH2) p -O-(CH2) q -OH In the formula, p is an integer of 1 to 3, and q is an integer of 1 to 3.
[0029] The method for producing polyester resin A having a structure represented by formula (1) is not particularly limited, and a known method can be used. For example, the above-mentioned divalent carboxylic acid component, divalent alcohol component, and silicone oil having a functional group are polymerized through an esterification reaction or an ester exchange reaction, and a condensation reaction to produce polyester resin A having a structure represented by formula (1). The polymerization temperature is not particularly limited, but is preferably in the range of 180° C. to 290° C. In polymerizing the polyester resin, for example, a polymerization catalyst such as a titanium-based catalyst, a tin-based catalyst, zinc acetate, antimony trioxide, or germanium dioxide can be used.
[0030] The toner particles preferably contain a crystalline polyester resin, which has high compatibility with the polyester moiety and therefore exhibits a plasticizing effect during fixing, resulting in good low-temperature fixing properties. Examples of alcohol components used as raw material monomers for the crystalline polyester resin include, but are not limited to, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-icosanediol. Among these, from the viewpoints of low-temperature fixability and folding resistance, aliphatic diols having 6 to 18 carbon atoms are preferred, and aliphatic diols having 8 to 14 carbon atoms are more preferred. The content of the aliphatic diol in the alcohol component is preferably 80 mol % or more and 100 mol % or less, from the viewpoint of further increasing the crystallinity of the crystalline polyester resin.
[0031] The alcohol component for obtaining the crystalline polyester resin may contain a polyhydric alcohol component other than the above-mentioned aliphatic diols. Examples of the polyoxypropylene adduct of 2,2-bis(4-hydroxyphenyl)propane and alkylene oxide adducts of bisphenol A, including polyoxyethylene adducts of 2,2-bis(4-hydroxyphenyl)propane, are mentioned; and trihydric or higher alcohols, such as glycerin, pentaerythritol, and trimethylolpropane.
[0032] On the other hand, examples of carboxylic acid components used as raw material monomers for crystalline polyester resins include aliphatic dicarboxylic acids such as oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid, as well as their anhydrides and lower alkyl esters.
[0033] Among these, from the viewpoints of low-temperature fixability and folding resistance, aliphatic dicarboxylic acids having 6 to 18 carbon atoms are preferred, and aliphatic dicarboxylic acids having 6 to 12 carbon atoms are more preferred. The content of the aliphatic dicarboxylic acid in the carboxylic acid component is preferably 80 mol % to 100 mol %.
[0034] The carboxylic acid component for obtaining the crystalline polyester resin may contain a carboxylic acid component other than the above-mentioned aliphatic dicarboxylic acid. For example, aromatic dicarboxylic acid, aromatic polyvalent carboxylic acid having three or more valences, etc. can be mentioned, but are not limited thereto. The aromatic dicarboxylic acid also includes aromatic dicarboxylic acid derivatives. Specific examples of aromatic dicarboxylic acids include phthalic acid, isophthalic acid, terephthalic acid, naphthaic acid, and the like. Examples of the alkyl group in the alkyl ester include aromatic dicarboxylic acids such as talen-2,6-dicarboxylic acid, anhydrides of these acids, and alkyl esters (having 1 to 3 carbon atoms). Examples of the alkyl group in the alkyl ester include methyl, ethyl, propyl, and isopropyl groups. Examples of trivalent or higher polyvalent carboxylic acids include aromatic carboxylic acids such as 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, and pyromellitic acid, as well as derivatives such as acid anhydrides and alkyl (carbon number 1 to 3) esters thereof. The molar ratio of the alcohol component and the carboxylic acid component, which are raw material monomers of the crystalline polyester resin (carboxylic acid component / alcohol component), is preferably 0.80 or more and 1.20 or less.
[0035] The content of the crystalline polyester resin is preferably 0.5 parts by mass or more and 10.0 parts by mass or less, and more preferably 3.0 parts by mass or more and 5.0 parts by mass or less, based on 100 parts by mass of the binder resin. By the content of the crystalline polyester resin being within the above range, it is possible to effectively obtain a plasticizing effect during fixing, and to improve low-temperature fixing properties. Furthermore, it is possible to effectively arrange a crystalline portion on the surface of the fixed image, and therefore the bending resistance is improved.
[0036] The toner can be used as any of magnetic one-component toner, non-magnetic one-component toner, and non-magnetic two-component toner. When used as a magnetic one-component toner, magnetic iron oxide particles are preferably used as a colorant. Examples of magnetic iron oxide particles contained in the magnetic one-component toner include magnetic iron oxides such as magnetite, maghemite, and ferrite, and magnetic iron oxides containing other metal oxides; metals such as Fe, Co, and Ni, or alloys of these metals with metals such as Al, Co, Cu, Pb, Mg, Ni, Sn, Zn, Sb, Be, Bi, Cd, Ca, Mn, Se, Ti, W, and V, and mixtures thereof. The content of the magnetic iron oxide particles is preferably 30 parts by mass or more and 150 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0037] Examples of colorants for use in non-magnetic one-component toners and non-magnetic two-component toners include the following. As black pigments, carbon blacks such as furnace black, channel black, acetylene black, thermal black, and lamp black are used, and magnetic powders such as magnetite and ferrite are also used. As a colorant suitable for yellow color, a pigment or a dye can be used. Examples of pigments include CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 17, 23, 62, 65, 73, 74, 81, 83, 93, 94, 95, 97, 98, 109, 110, 111, 117, 120, 127, 128, 129, 137, 138, 139, 147, 151, 154, 155, 167, 168, 173, 174, 176, 180, 181, 183, 191, and CI Bat Yellow 1, 3, and 20. Examples of dyes include CI Solvent Yellow 19, 44, 77, 79, 81, 82, 93, 98, 103, 104, 112, and 162. These may be used alone or in combination of two or more.
[0038] As a colorant suitable for cyan, a pigment or a dye can be used. Examples of pigments include CI Pigment Blue 1, 7, 15, 15;1, 15;2, 15;3, 15;4, 16, 17, 60, 62, 66, etc., CI Vat Blue 6, and CI Acid Blue 45. Examples of dyes include CI Solvent Blue 25, 36, 60, 70, 93, 95, etc. These can be used alone or in combination of two or more. As a colorant suitable for magenta, a pigment or a dye can be used. Pigments include CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12. ,13,14,15,16,17,18,19,21,22,23,30,31,32,37,38,39,40,41,48,48;2,48;3,48;4,49,50,51,52,53,54,55,57,57;1,58,60,63,64,68,81,81;1,83,87,88,89,9 0, 112, 114, 122, 123, 144, 146, 150, 163, 166, 169, 177, 184, 185, 202, 206, 207, 209, 220, 221, 238, 254, etc.; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35. Examples of dyes for magenta include oil-soluble dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 52, 58, 63, 81, 82, 83, 84, 100, 109, 111, 121, 122, CI Disperse Red 9, CI Solvent Violet 8, 13, 14, 21, 27, CI Disperse Violet 1, and basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40, CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28. These dyes can be used alone or in combination of two or more. The content of the colorant is preferably 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0039] In order to impart releasability to the toner, a release agent (wax) may be used. Examples of waxes include the following: aliphatic hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, olefin copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxidized waxes of aliphatic hydrocarbon waxes such as oxidized polyethylene wax; waxes mainly composed of fatty acid esters such as carnauba wax, behenyl behenate, and montan acid ester wax; and waxes in which fatty acid esters have been partially or completely deoxidized, such as deoxidized carnauba wax. In addition, saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and valinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; saturated fatty acid bisamides such as methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, and hexamethylene bisstearic acid amide; ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N Examples of such compounds include unsaturated fatty acid amides such as N,N'-dioleyl adipamide and N,N'-dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearamide and N,N'-distearyl isophthalamide; fatty metal salts such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate (commonly known as metal soaps); waxes grafted onto aliphatic hydrocarbon waxes using vinyl copolymer monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols, such as behenic acid monoglyceride; and methyl ester compounds having hydroxy groups obtained by hydrogenating vegetable oils and fats.
[0040] Waxes that are particularly preferably used in the present invention are aliphatic hydrocarbon waxes. For example, low molecular weight hydrocarbons obtained by radical polymerization of alkylene under high pressure or polymerization with a Ziegler catalyst or a metallocene catalyst under low pressure; Fischer-Tropsch wax synthesized from coal or natural gas; olefin polymers obtained by pyrolysis of high molecular weight olefin polymers; synthetic hydrocarbon waxes obtained from the distillation residue of hydrocarbons obtained by the Arge process from synthesis gas containing carbon monoxide and hydrogen; and synthetic carbon waxes obtained by hydrogenating these. Hydrogenated waxes are preferred. Further, those obtained by fractionating the hydrocarbon wax using the press sweating method, the solvent method, vacuum distillation, or fractional crystallization are more preferably used. Waxes synthesized by methods other than the polymerization of alkylene are particularly preferred in terms of their molecular weight distribution. The wax may be added during the production of the toner or during the production of the binder resin. The wax may be used alone or in combination of two or more. The wax is preferably added in an amount of 1 part by mass or more and 20 parts by mass or less per 100 parts by mass of the binder resin.
[0041] The toner may contain a charge control agent. Known charge control agents may be used, such as azo iron compounds, azo chromium compounds, azo manganese compounds, azo cobalt compounds, azo zirconium compounds, chromium compounds of carboxylic acid derivatives, zinc compounds of carboxylic acid derivatives, aluminum compounds of carboxylic acid derivatives, and zirconium compounds of carboxylic acid derivatives. The carboxylic acid derivative is preferably an aromatic hydroxycarboxylic acid. A charge control resin can also be used. If necessary, one or more types of charge control agents may be used in combination. The charge control agent is preferably used in an amount of 0.1 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the binder resin.
[0042] The toner may be mixed with a carrier to be used as a two-component developer. As the carrier, a carrier such as a normal ferrite or magnetite or a resin-coated carrier may be used. A binder-type carrier core in which magnetic powder is dispersed in a resin may also be used.
[0043] The resin-coated carrier is composed of carrier core particles and a coating material which is a resin that coats the surface of the carrier core particles. Examples of resins used in the coating material include styrene-acrylic resins such as styrene-acrylic acid ester copolymers and styrene-methacrylic acid ester copolymers; acrylic resins such as acrylic acid ester copolymers and methacrylic acid ester copolymers; fluorine-containing resins such as polytetrafluoroethylene, monochlorotrifluoroethylene polymers, and polyvinylidene fluoride; silicone resins; polyester resins; polyamide resins; polyvinyl butyral; and aminoacrylate resins. Other examples include ionomer resins and polyphenylene sulfide resins. These resins can be used alone or in combination.
[0044] In order to improve the charge stability, developability, fluidity, and durability, it is preferable to externally add silica fine powder to the toner particles. The silica fine powder has a specific surface area of 30 m2 or less as measured by the BET method using nitrogen adsorption. 2 / g or more 500m 2 / g or less, and 2 / g or more 400m 2 It is more preferable that the molecular weight is not more than 1 / g. Further, the silica fine powder is preferably used in an amount of 0.01 parts by mass or more and 8.00 parts by mass or less, and more preferably 0.10 parts by mass or more and 5.00 parts by mass or less, based on 100 parts by mass of the toner particles.
[0045] The BET specific surface area of the silica fine powder can be calculated by adsorbing nitrogen gas onto the surface of the silica fine powder using, for example, a specific surface area measuring device such as Autosorb 1 (manufactured by Yuasa Ionics), GEMINI 2360 / 2375 (manufactured by Micrometilix), or Tristar 3000 (manufactured by Micrometilix), and then using the BET multi-point method. The silica fine powder may be treated, as necessary, with a treatment agent such as unmodified silicone varnish, various modified silicone varnishes, unmodified silicone oil, various modified silicone oils, a silane coupling agent, a silane compound having a functional group, or other organic silicon compounds, or may be treated in combination with various treatment agents, for the purpose of hydrophobization and triboelectric charge control. I wish.
[0046] Other external additives may be added to the toner as necessary. Examples of such external additives include resin fine particles and inorganic fine powders that act as charge assistants, conductivity-imparting agents, fluidity-imparting agents, caking prevention agents, release agents during heat roller fixing, lubricants, abrasives, etc. Examples of charge assistants include metal oxides such as titanium oxide, zinc oxide, and alumina. Examples of lubricants include polyethylene fluoride powder, zinc stearate powder, and polyvinylidene fluoride powder. Examples of abrasives include cerium oxide powder, silicon carbide powder, and strontium titanate powder.
[0047] The method for producing the toner particles is not particularly limited, and examples thereof include a pulverization method, an emulsion aggregation method, a suspension polymerization method, a dissolution suspension method, etc. From the viewpoint of dispersion of toner materials such as pigments, the pulverization method is preferred. Below, the method for producing the toner will be described taking the pulverization method as an example, but is not limited thereto. The method for producing the toner preferably comprises the steps of: A step of mixing a polyester resin including a polyester resin A having a structure represented by formula (1), and, if necessary, a colorant, a crystalline polyester resin, and other additives, etc.; The method includes a step of melting and kneading the mixture, and a step of cooling and solidifying the melted and kneaded mixture, followed by pulverization and, if necessary, classification to obtain toner particles. In the melt-kneading step, wax, magnetic iron oxide particles and a metal-containing compound may be added.
[0048] Examples of mixers include the following: Henschel Mixer (manufactured by Mitsui Mining Co., Ltd.), Super Mixer (manufactured by Kawata Co., Ltd.), Ribocone (manufactured by Okawara Manufacturing Co., Ltd.), Nauta Mixer, Turbulizer, Cyclomix (manufactured by Hosokawa Micron Corporation), Spiral Pin Mixer (manufactured by Pacific Machinery Co., Ltd.), and Loedige Mixer (manufactured by Matsubo Co., Ltd.). Examples of kneading machines include the following: KRC kneader (Kurimoto Iron Works); Buss-Co kneader (Buss); TEM type extruder (Toshiba Machine); TEX twin-screw kneader (Japan Steel Works); PCM kneader (Ikegai Iron Works); three-roll mill, mixing roll mill, kneader (Inoue Seisakusho); Kneadex (Mitsui Mining); MS-type pressure kneader, Niderruder (Moriyama Seisakusho); Banbury mixer (Kobe Steel, Ltd.).
[0049] Examples of pulverizers include the following: Counter Jet Mill, Micron Jet, Innomizer (manufactured by Hosokawa Micron Corporation); IDS type mill, PJM jet pulverizer (manufactured by Nippon Pneumatic Mfg. Co., Ltd.); Cross Jet Mill (manufactured by Kurimoto Iron Works Co., Ltd.); Urmax (manufactured by Nisso Engineering Co., Ltd.); SK Jet-O-Mill (manufactured by Seishin Enterprise Co., Ltd.); Cryptron (manufactured by Kawasaki Heavy Industries, Ltd.); Turbo Mill (manufactured by Turbo Kogyo Co., Ltd.); and Super Rotor (manufactured by Nisshin Engineering Co., Ltd.). Examples of classifiers include the following: Classeal, Micron Classifier, and Spedic Classifier (manufactured by Seishin Enterprise Co., Ltd.); Turbo Classifier (manufactured by Nisshin Engineering Co., Ltd.); Micron Separator, Turboplex (ATP), and TSP Separator (manufactured by Hosokawa Micron Corporation); Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), Dispersion Separator (manufactured by Nippon Pneumatic Mfg. Co., Ltd.); and YM Microcut (manufactured by Yaskawa Shoji Co., Ltd.).
[0050] Here, by subjecting the toner particles to a heat treatment in the process of obtaining the toner particles, a gradient in the amount of silicone moieties can be formed so that the amount of silicone moieties decreases from the surface to the inside of the toner. For example, the toner particles obtained by the pulverization method can be subjected to a heat treatment. The toner manufacturing method preferably includes a step of heat treating the toner particles. Since the silicone moiety has low affinity with the polyester unit, it is difficult to form the silicone moiety in the flow field caused by heat treatment. As a result, the amount of silicone moieties increases near the toner particle surface, and the amount of silicone moieties tends to decrease inside the toner particle.
[0051] For example, the surface treatment can be performed with hot air using the surface treatment device shown in FIG. The mixture supplied by the material supply means 1 is introduced into an introduction pipe 3, which is installed vertically to the material supply means, by compressed gas adjusted by a compressed gas adjustment means 2. The mixture passing through the introduction pipe is uniformly dispersed by a conical protruding member 4 installed in the center of the material supply means, and is introduced into eight supply pipes 5 that radiate outward, and then into a treatment chamber 6 where heat treatment is carried out. At this time, the flow of the mixture supplied to the treatment chamber is regulated by a regulating means 9 for regulating the flow of the mixture provided in the treatment chamber. Therefore, the mixture supplied to the treatment chamber is heat-treated while swirling in the treatment chamber, and then cooled. Hot air for heat-treating the supplied mixture is supplied from hot air supplying means 7, and is introduced into the treatment chamber by spirally swirling the hot air using a swirling member 13 for swirling the hot air. In terms of its configuration, the swirling member 13 for swirling the hot air has a plurality of blades, and the swirling of the hot air can be controlled by the number and angle of the blades. The hot air supplied into the treatment chamber preferably has a temperature of 100°C to 300°C at the outlet of the hot air supplying means 7. The temperature is more preferably 165°C to 190°C. If the temperature at the outlet of the hot air supplying means is within the above range, it is possible to prevent the fusion and coalescence of toner particles caused by overheating the mixture, and it is also possible to promote the fluidization of the silicone moieties in the toner, making it easier to impart a gradient in the amount of silicone moieties from the surface to the interior of the toner.
[0052] The heat-treated toner particles are then cooled by cold air supplied from cold air supply means 8 (8-1, 8-2, 8-3), and the temperature of the cold air supplied from the cold air supply means 8 is preferably -20°C to 30°C. If the temperature of the cold air is within the above range, the heat-treated toner particles can be efficiently cooled, and the fusion and coalescence of the heat-treated toner particles can be prevented. The absolute moisture content of the cold air is 0.5 g / m 3 More than 15.0g / m 3 It is preferable that: Next, the cooled heat-treated toner particles are collected by the collecting means 10 at the bottom end of the processing chamber. A blower (not shown) is provided ahead of the collecting means, so that the toner particles are sucked and transported by the blower.
[0053] The powder particle supply port 14 is provided so that the swirling direction of the supplied mixture and the swirling direction of the hot air are the same, and the recovery means 10 of the surface treatment device is provided on the outer periphery of the treatment chamber so as to maintain the swirling direction of the swirled powder particles. Furthermore, the cold air supplied from the cold air supply means 8 is configured to be supplied horizontally and tangentially from the outer periphery of the device to the circumferential surface inside the treatment chamber. The swirling direction of the toner particles supplied from the powder supply port, the swirling direction of the cold air supplied from the cold air supply means, and the swirling direction of the hot air supplied from the hot air supply means are all the same, so no turbulence occurs in the processing chamber, the swirling flow in the device is strengthened, a strong centrifugal force is applied to the toner particles, and the dispersibility of the toner particles is further improved, so that a toner with a uniform shape and few coalesced particles can be obtained.
[0054] The obtained toner particles may be used as they are as a toner, or, if necessary, the toner particles may be mixed with an external additive in a mixer such as a Henschel mixer to obtain a toner. The external additive may be mixed before or after the heat treatment of the toner particles, or may be mixed both before and after the heat treatment.
[0055] Next, the measurement methods for each physical property will be described. <Measurement of glass transition temperature (Tg)> The Tg of the resin or toner is measured using a differential scanning calorimeter "Q2000" (manufactured by TA Instruments) in accordance with ASTM D3418-82. The melting points of indium and zinc are used for temperature correction of the device detection section, and the heat of fusion of indium is used for heat correction. Specifically, about 3 mg of a sample is precisely weighed and placed in an aluminum pan, and measurement is performed under the following conditions using an empty aluminum pan as a reference. Heating rate: 10℃ / min Measurement start temperature: 30℃ End of measurement temperature: 180℃ Measurements are performed in the measurement range of 30 to 180°C at a heating rate of 10°C / min. The temperature is raised to 180°C once and held for 10 minutes, then cooled to 30°C, and then raised again. During this second heating process, the specific heat change is obtained in the temperature range of 30 to 100°C. The point at which the line midway between the baselines before and after the specific heat change appears and the differential heat curve intersects is the glass transition temperature (Tg) of the sample.
[0056] <Method for measuring softening point Tm> The softening point is measured using a constant load extrusion type capillary rheometer "Flow property evaluation device Flow Tester CFT-500D" (Shimadzu Corporation) according to the manual that comes with the device. With this device, a constant load is applied from above the measurement sample by a piston while the measurement sample filled in a cylinder is heated and melted, and the molten measurement sample is extruded from a die at the bottom of the cylinder, and a flow curve showing the relationship between the piston descent amount and temperature can be obtained. The "melting temperature in the 1 / 2 method" described in the manual attached to the "Flow characteristic evaluation device Flow Tester CFT-500D" is taken as the softening point. The melting temperature in the 1 / 2 method is calculated as follows. First, half the difference between the amount of piston descent Smax at the time when the outflow ends and the amount of piston descent Smin at the time when the outflow starts is calculated (this is called X; X=(Smax-Smin) / 2). Then, the temperature of the flow curve when the amount of piston descent on the flow curve is the sum of X and Smin is the melting temperature Tm (°C) in the 1 / 2 method. The measurement sample is prepared by compressing approximately 1.3 g of the sample at approximately 10 MPa for approximately 60 seconds using a tablet molding machine (e.g., NT-100H, manufactured by NPA Systems) in an environment of 25°C to form a cylindrical shape with a diameter of approximately 8 mm. The measurement conditions for the CFT-500D are as follows. Test mode: Temperature rise method Starting temperature: 50℃ Achieved temperature: 200℃ Measurement interval: 1.0℃ Heating rate: 4.0℃ / min Piston cross-sectional area: 1.000cm 2 Test load (piston load): 10.0kgf / cm 2 (0.9807MPa) Preheat time: 300 seconds Die hole diameter: 1.0mm Die length: 1.0mm
[0057] <Measurement of weight average particle size (D4) of toner particles> The weight average particle diameter (D4) of the toner particles was measured using a precision particle size distribution measuring device "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.) equipped with a 100 μm aperture tube and using the narrow hole electrical resistance method. Using the dedicated analysis software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter), measurements are taken with an effective number of measurement channels of 25,000, and the measurement data is analyzed and calculated. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter). Before carrying out the measurements and analyses, the dedicated software is set up as follows. In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.
[0058] The specific measurement method is as follows. (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) Approximately 30 ml of the above-mentioned aqueous electrolyte solution is placed in a 100 ml flat-bottom glass beaker, and approximately 0.3 ml of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, with a pH of 7, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water is added as a dispersant. (3) A predetermined amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the Conaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner particles are added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) In the round-bottom beaker (1) placed in the sample stand, the electrolyte solution (5) in which the toner particles are dispersed is dropped using a pipette to adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4).
[0059] <Measurement of amount X and ratio Y of silicone part> (Pretreatment) A sucrose solution prepared by dissolving 20.7 g of sucrose (Kishida Chemical Co., Ltd.) in 10.3 g of ion-exchanged water and 6 mL of the surfactant Contaminon N (a neutral detergent for cleaning precision measuring instruments with a pH of 7 consisting of a nonionic surfactant, an anionic surfactant, and an organic builder; Wako Pure Chemical Industries, Ltd.) are placed in a 30 mL glass vial (e.g., VCV-30, manufactured by Nichiden Rika Glass Co., Ltd., outer diameter: 35 mm, height: 70 mm) and mixed thoroughly to prepare a dispersion. 1.0 g of toner is added to this vial, and the toner is left to stand until it naturally settles to prepare a pre-treatment dispersion. This dispersion is shaken for 5 minutes at a shaking speed of 200 rpm using a shaker (YS-8D type: manufactured by Yayoi Co., Ltd.) to separate the external additive particles from the toner particle surface. Then, the dispersion is centrifuged at 3700 rpm for 30 minutes using a centrifuge to separate the detached external additive particles, and the toner particles are collected by suction filtration and dried.
[0060] (Measurement of the amount of silicone moieties using an X-ray photoelectron spectroscopy (XPS)) The toner particle powder that has been subjected to the measurement pretreatment is fixed to the sample stage of the XPS device using an indium sheet, and measurement is performed under the following conditions. Equipment used: ULVAC-PHI PHI 5000VersaProbe II Irradiation: Al-Kα radiation Output: 100μm, 25W, 15kV Photoelectron capture angle: 45° PassEnergy: 58.70eV Step size: 0.125eV Measurement target elements: All elements detected Measurement range: Powder 300μm x 200μm (Sputtering conditions) Sputter ion gun: Ar gas cluster ion beam Accelerating voltage: 20 kV Sputtering area: 5mm x 5mm It should be noted that sputtering is not used when analyzing the surface of toner particles.
[0061] The ratio (x100) of the number of silicon atoms derived from (attributed to) the silicone moiety to the total number of atoms obtained under the above conditions is defined as the amount of silicone moieties, X (atomic %). If any silica from the external additive remains that was not removed by the pretreatment, the peaks of silica and silicone moieties are separated by peak separation of the Si2p photoelectron spectrum to calculate the number of silicon atoms derived from the silicone moieties. In addition, the number of carbon atoms attributable to ester bonds is calculated by peak separation of the C1s photoelectron spectrum, and the ratio (×100) of the number of carbon atoms to the total number of atoms is defined as the ratio (Z) of the number of carbon atoms derived from (attributed to) ester bonds in the polyester resin to the total number of atoms. The ratio Y is the value (X / Z) obtained by dividing the amount X of the silicone moiety obtained above by Z. X / Z (i.e., X1 / Z1) on the toner surface is defined as Y1. Regarding the "depth" from the toner particle surface, first, the relationship between the sputtering time and the sputtering depth obtained by sputtering a polyester film of known thickness under the above conditions is calculated. Based on the obtained relationship, the powder of the toner particles is sputtered under the above conditions for a time to obtain the desired depth. Then, XPS analysis is performed under the above conditions to calculate the value of the ratio Y at a position of 10 nm, 20 nm, or 30 nm deep from the surface of the toner particles (i.e., Y2, Y3, and Y4).
[0062] <Measurement of Polyester Resin and Crystalline Polyester Resin Content in Toner> As described below, the above materials can be separated from the toner by utilizing the difference in solubility in a solvent, and the content of each material can be determined. First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23°C, and the soluble portion (binder resin) is separated from the insoluble portion (crystalline polyester resin, release agent, colorant, inorganic fine particles, etc.). The binder resin separated as the soluble portion is thoroughly dried to remove the solvent, and then the mass is measured to determine the binder resin content. Next, the monomers contained in the binder resin component were qualitatively analyzed by pyrolysis gas chromatography mass spectrometry at 590°C. 1 The content of the polyester resin in the binder resin can be determined by calculating the molar ratio of each monomer by H-NMR. Second separation: The insoluble matter obtained in the first separation (crystalline polyester resin, release agent, colorant, inorganic fine particles) is dissolved in MEK at 100°C, and the soluble matter (crystalline polyester resin, release agent) is separated from the insoluble matter (colorant, inorganic fine particles). Third separation: The soluble matter (crystalline polyester resin, release agent) obtained in the second separation is dissolved in chloroform at 23°C, and the crystalline polyester resin is separated as the soluble matter. After the solvent is thoroughly dried and removed, the mass is measured to determine the content of the crystalline polyester resin.
[0063] <Confirmation of the Structure of Polyester Resin A Having the Structure Represented by Formula (1)> The structure of polyester resin A having the structure represented by formula (1) is confirmed by the following method. R in Equation (1) X The hydrocarbon group and silicone moiety are 13 C-NMR and solid state 29 Confirm by Si-NMR. ( 13 C-NMR measurement conditions) Equipment: JEOL RESONANCE JNM-ECX500II Sample tube: 3.2mmφ Sample: Deuterated chloroform soluble fraction of sample for NMR measurement Measurement temperature: room temperature Pulse mode: CP / MAS Measurement nuclear frequency: 123.25MHz ( 13 C) Reference substance: Adamantane (external standard: 29.5ppm) Sample rotation speed: 20kHz Contact time: 2ms Delay time: 2s Number of times accumulated: 1024 In this method, the presence or absence of signals due to methyl groups (Si-CH3) or phenyl groups (Si-C6H5) bonded to silicon atoms can be used to determine the R X Identify the hydrocarbon groups.
[0064] solid 29 Specifically, the Si-NMR measurement conditions are as follows: Equipment: JNM-ECX5002 (JEOL RESONANCE) Temperature: room temperature Measurement method: DD / MAS method29 Si 45° Sample tube: Zirconia 3.2mmφ Sample: Powdered material filled into test tube Sample rotation speed: 10kHz Relaxation delay: 180s Scan:2000 EXAMPLES
[0065] The present invention will be specifically described below based on examples. However, the present invention is not limited thereto. In the following formulations, parts are by weight unless otherwise specified.
[0066] <Production Example of Polyester Resin (Binder Resin 1) Having a Structure Represented by Formula (1)> Bisphenol A ethylene oxide (2.2 mole adduct): 50.0 mole parts Bisphenol A propylene oxide (2.2 mole adduct): 50.0 mole parts Terephthalic acid: 90.0 parts by mole Trimellitic anhydride: 10.0 mol parts 97 parts of the above monomer for forming the polyester portion and a copolymer having hydroxy groups at both ends Four parts of silicone oil (KF-6001, Shin-Etsu Chemical Co., Ltd.) were mixed with 500 ppm of titanium tetrabutoxide in a 5-liter autoclave. According to KF-6001, in formula (1), R X are both methyl groups, resulting in a structure where n is 38. A reflux condenser, a moisture separator, an N2 gas inlet tube, a thermometer and an agitator were attached to the autoclave, and a condensation polymerization reaction was carried out at 230°C while introducing N2 gas into the autoclave. After the reaction was completed, the mixture was taken out of the vessel, cooled and pulverized to obtain binder resin 1, which is polyester resin A having a structure represented by formula (1).
[0067] <Production example of polyester resin (binder resin 2)> Bisphenol A ethylene oxide (2.2 mole adduct): 50.0 mole parts Bisphenol A propylene oxide (2.2 mole adduct): 50.0 mole parts Terephthalic acid: 90.0 parts by mole Trimellitic anhydride: 10.0 mol parts The monomers constituting the polyester unit were mixed together with 500 ppm of titanium tetrabutoxide in a 5-liter autoclave. A reflux condenser, a moisture separator, an N2 gas inlet pipe, a thermometer and an agitator were attached to the autoclave, and a condensation polymerization reaction was carried out at 230° C. while introducing N2 gas into the autoclave. After the reaction was completed, the contents were removed from the vessel, cooled and pulverized to obtain binder resin 2, which was a polyester resin.
[0068] <Production example of styrene acrylic resin (binder resin 3)> Styrene: 70.0 parts by mole 2-Ethylhexyl acrylate: 30.0 parts by mole A mixture of 100 parts of monomer for constituting the above styrene-acrylic resin and 5 parts of benzoyl peroxide as a polymerization initiator was dropped into 200 parts of heated xylene over 4 hours. Polymerization was completed under reflux of xylene, and the solvent was distilled off under reduced pressure. After the reaction was completed, the mixture was removed from the vessel, cooled, and pulverized to obtain binder resin 3, which was a styrene-acrylic resin.
[0069] <Production Example of Crystalline Polyester Resin> In a reaction vessel equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, 100.0 mol parts of 1,10-decanedicarboxylic acid as a carboxylic acid monomer and 100.0 mol parts of 1,9-nonanediol as an alcohol monomer were charged. The temperature was raised to 140°C with stirring, and the mixture was heated to 140°C under a nitrogen atmosphere and reacted for 8 hours while distilling off water under normal pressure. Next, 0.57 parts of tin dioctylate was added, and the mixture was reacted while heating to 200°C at a rate of 10°C / hour. After the reaction was continued for 2 hours after reaching 200°C, the pressure in the reaction vessel was reduced to 5 kPa or less, and the mixture was reacted at 200°C while monitoring the molecular weight, to obtain a crystalline polyester resin. The obtained crystalline polyester resin had a clear endothermic peak in DSC measurement.
[0070] (Toner 1 manufacturing example) Binding resin 1 100 parts Binder resin 2 20 parts Crystalline polyester resin 5.0 parts Fischer-Tropsch wax (melting point: 90°C) 6.0 parts CI Pigment Blue 15:3 4.0 parts The above materials were premixed in a Henschel mixer, and then melt-kneaded at 160° C. in a twin-screw kneading extruder. The resulting kneaded product was cooled, coarsely pulverized in a hammer mill, and then finely pulverized in a turbo mill. The resulting finely pulverized material is classified using a multi-division classifier utilizing the Coanda effect to obtain a toner matrix. particles were obtained. For 100 parts of the toner base particles, hydrophobically treated silica fine particles (with a specific surface area of 140 m2 measured by nitrogen adsorption using the BET method) were 2 The mixture was mixed with a Henschel mixer, and then heat-treated with the surface treatment device shown in FIG. 1 to obtain heat-treated toner particles. The operating conditions were feed rate of 5 kg / h, hot air temperature of 180° C., and hot air flow rate of 6 m 3 / min., cold air temperature = -5℃, cold air flow rate = 4m 3 / min., Blower air volume = 20m 3 / min., Injection air flow rate = 1m 3 / min. The obtained heat-treated toner particles were classified using an elbow jet of an inertial classification method to obtain heat-treated toner particles having a weight average particle size of 6.0 μm. For 100 parts of the heat-treated toner particles, hydrophobized silica fine particles (with a specific surface area of 140 m2 measured by nitrogen adsorption using the BET method) were2 The mixture was mixed using a Henschel mixer, and then sieved through a 150 μm mesh to obtain negatively triboelectrically charged toner 1. Toner 1 had a Tm of 135° C. and a Tg of 56° C.
[0071] (Example of manufacturing magnetic core particles) (Step 1: Weighing and mixing step) ·Fe2O362.7 parts ·MnCO329.5 parts ·Mg(OH)26.8 parts ·SrCO31.0 parts The ferrite raw materials were weighed so as to obtain the above-mentioned composition ratio, and then crushed and mixed for 5 hours in a dry vibration mill using stainless steel beads with a diameter of 1 / 8 inch. (Step 2: Pre-firing step) The obtained pulverized material was made into pellets of about 1 mm square using a roller compactor. The pellets were passed through a vibrating sieve with 3 mm openings to remove coarse powder, and then passed through a vibrating sieve with 0.5 mm openings to remove fine powder. The pellets were then fired in a burner-type firing furnace at 1000°C for 4 hours in a nitrogen atmosphere (oxygen concentration 0.01% by volume) to produce calcined ferrite. The composition of the resulting calcined ferrite was as follows: (MnO) a (MgO) b (SrO) c (Fe2O3) d In the above formula, a = 0.257, b = 0.117, c = 0.007, d = 0.393
[0072] (Step 3: Crushing step) The calcined ferrite was crushed to about 0.3 mm using a crusher, and then 30 parts of water was added to 100 parts of the calcined ferrite and crushed in a wet ball mill using zirconia beads with a diameter of 1 / 8 inch for 1 hour. The resulting slurry was then crushed in a wet ball mill using alumina beads with a diameter of 1 / 16 inch for 4 hours to obtain a ferrite slurry (finely crushed calcined ferrite). (Process 4: Granulation process) To the ferrite slurry, 1.0 part of ammonium polycarboxylate as a dispersant and 2.0 parts of polyvinyl alcohol as a binder were added to 100 parts of the calcined ferrite. Then, the mixture was granulated into spherical particles using a spray dryer (manufacturer: Okawara Kakoki Co., Ltd.). After adjusting the particle size of the obtained particles, the mixture was heated at a temperature of 650°C for 2 hours using a rotary kiln to remove the organic components of the dispersant and binder.
[0073] (Step 5: Firing step) In order to control the firing atmosphere, the material was heated from room temperature to 1300°C in a nitrogen atmosphere (oxygen concentration 1.00% by volume) in an electric furnace over a period of 2 hours, and then fired at 1150°C for 4 hours. The material was then cooled to 60°C over a period of 4 hours, returned from the nitrogen atmosphere to the air, and removed at a temperature of 40°C or less. (Step 6: Sorting step) After crushing the agglomerated particles, low magnetic particles were removed by magnetic separation, and coarse particles were removed by sieving through a sieve with 250 μm openings to obtain magnetic core particles with a 50% particle size based on volume distribution of 37.0 μm.
[0074] (Example of coating resin production) Cyclohexyl methacrylate 26.8% by mass Methyl methacrylate 0.2% by mass Methyl methacrylate macromonomer 8.4% by mass (A macromonomer with a weight-average molecular weight of 5000 and a methacryloyl group at one end) Toluene 31.3% by mass Methyl ethyl ketone 31.3% by mass Azobisisobutyronitrile 2.0% by mass Of the above materials, cyclohexyl methacrylate, methyl methacrylate, methyl methacrylate macromonomer, toluene, and methyl ethyl ketone were placed in a four-neck separable flask equipped with a reflux condenser, a thermometer, a nitrogen inlet tube, and a stirrer. Nitrogen gas was introduced into the separable flask to create a sufficient nitrogen atmosphere, and the flask was then heated to 80° C., azobisisobutyronitrile was added, and the mixture was refluxed for 5 hours to polymerize. Hexane was poured into the reaction product to precipitate the copolymer, which was then filtered and dried in vacuum to obtain a coating resin. 30 parts of the coating resin was dissolved in a mixed solvent of 40 parts of toluene and 30 parts of methyl ethyl ketone to obtain a resin solution (solid content concentration: 30%).
[0075] (Preparation of coating resin solution) ·Resin solution (solid content concentration 30%) 33.3% by mass Toluene 66.4% by mass Carbon black (Regal 330; Cabot Corporation) 0.3% by mass (Number average particle size of primary particles: 25 nm, Nitrogen adsorption specific surface area: 94 m 2 / g, DBP oil absorption: 75ml / 100g) The above materials were placed in a paint shaker and dispersed for 1 hour using zirconia beads having a diameter of 0.5 mm. The resulting dispersion was filtered through a 5.0 μm membrane filter to obtain a coating resin solution.
[0076] (Magnetic carrier manufacturing example) The coating resin solution and magnetic core particles were charged into a vacuum degassing kneader maintained at room temperature (the amount of the coating resin solution charged was 2.5 parts as the resin component per 100 parts of the magnetic core particles). After the addition, the mixture was stirred at a rotation speed of 30 rpm for 15 minutes. After a certain amount of the solvent had evaporated (80%), the mixture was heated to 80°C while mixing under reduced pressure, and the toluene was distilled off over 2 hours, after which the mixture was cooled. The obtained magnetic carrier was subjected to magnetic separation to separate out low magnetic particles, which were passed through a sieve with 70 μm openings and then classified with an air classifier to obtain magnetic carrier particles having a 50% particle size based on volume distribution of 38.2 μm.
[0077] <Production example of developer 1> The toner 1 and magnetic carrier were mixed in a V-type mixer (V-10 type: Tokuju Seisakusho Co., Ltd.) at a ratio of 90 parts magnetic carrier to 10 parts toner 1 for 0.5 seconds. -1 The developer 1 was prepared by mixing under the conditions of 1000 g for a rotation time of 5 minutes. The resulting developer 1 was used for the following evaluations.
[0078] <Evaluation of releasability (sticking of paper to fixing material)> As an image forming device, Canon's digital commercial printer imageRUNNE A R ADVANCE C5051 was used and modified so that the fixing temperature and process speed could be freely set. Developer 1 was placed in the developer unit in the cyan position of this modified machine, and the DC voltage VDC of the developer carrier, the charging voltage VD of the electrostatic latent image carrier, and the laser power were adjusted so that the amount of toner carried on the electrostatic latent image carrier or paper was as desired, and the evaluation described below was performed. Paper: CS-680 (68.0g / m 2 ) (Sold by Canon Marketing Japan Inc.) Toner load on paper: 1.20mg / cm 2 Evaluation image: A 2cm x 29cm image placed at the 5mm leading edge margin of the A4 paper. Fixing test environment: High temperature and humidity environment: Temperature 30℃ / Humidity 80%RH (hereinafter referred to as "H / H") The process speed was set to 450 mm / sec, the fixing temperature was adjusted to output a fixed image, and visual observation was made to see whether wrapping occurred during fixing. The upper limit temperature at which wrapping was not observed was determined as the fixation separation temperature. The fixation separation temperature was evaluated according to the following criteria. (Evaluation Criteria) A: The fixing and separation temperature is 130℃ or higher. B: The fixing separation temperature is lower than 130°C and higher than 125°C. C: The fixing separation temperature is lower than 125°C and higher than 120°C. D: The fixing / separating temperature is lower than 120°C.
[0079] <Bending resistance> The optimum fixing temperature is set to 20°C higher than the lowest fixing temperature, and the paper is GF-C209 (A4 209g / cm 2 ) (sold by Canon Marketing Japan Inc.), with a toner load of 0.90 mg / cm on one side of A4 paper. 2 A solid image was formed on the recording paper, and the recording paper on which the solid image was formed was folded crosswise. The folded image area was rubbed back and forth five times with Silbon paper under a load of 4.9 kPa, and the area ratio of the peeled image area was calculated to evaluate the foldability. (Evaluation Criteria) A: The area ratio of peeled parts is less than 5% B: The area ratio of peeled parts is 5% or more and less than 10% C: The area ratio of peeled parts is 10% or more and less than 20% D: The area ratio of peeled parts is 20% or more.
[0080] <Evaluation of low-temperature fixability> As an image forming device, a Canon digital commercial printing printer imageRUNNER ADVANCE C5051 was used, which was modified so that the fixing temperature and process speed could be freely set. Developer 1 was placed in the developer unit in the cyan position of this modified machine, and the DC voltage VDC of the developer carrier, the charging voltage VD of the electrostatic latent image carrier, and the laser power were adjusted so that the amount of toner on the electrostatic latent image carrier or paper was as desired, and the evaluation described below was performed. Paper: CS-680 (68.0g / m 2 ) (Sold by Canon Marketing Japan Inc.) Toner load on paper: 0.90mg / cm 2 Evaluation image: 10cm from the center of the A4 paper above 2 Place the image Fixing test environment: Low temperature and low humidity environment: Temperature 15℃ / Humidity 10%RH (hereinafter referred to as "L / L") The process speed was set to 450 mm / sec, the fixing temperature was adjusted, and a fixed image was output, and the state of the fixed image was visually evaluated. (Evaluation Criteria) A: Fixing is possible in the temperature range below 115℃. B: Fixing is possible in the temperature range higher than 115°C and lower than 120°C. C: Fixing is possible in the temperature range higher than 120℃ and lower than 125℃. D: Fixable only in the temperature range above 125°C.
[0081] In each of the above evaluation items, Developer 1 was rated A in all cases. <Examples 2 to 7> (Production Examples of Toners 2 to 7) Toners 2 to 7 were obtained in the same manner as in the production example of toner 1, except that the type of binder resin and the amount of crystalline polyester resin were changed, and the heat treatment conditions of the toner were changed so that the amount X1 of the silicone moiety and the ratio Y were as shown in Table 1. The heat treatment conditions were changed as follows: For toner 2, the hot air temperature was 178° C. For toners 3 and 4, the hot air temperature was 175° C., for toners 5 and 6, the hot air temperature was 170° C., and for toner 7, the hot air temperature was 170° C. The other heat treatment conditions were the same as those for toner 1.
[0082] [Table 1] In Tables 1 and 3, "Content of crystalline polyester resin" indicates the number of parts per 100 parts of binder resin. "Reduction rate of ratio Y" indicates the reduction rate of the value of ratio Y at a depth position shown in Table 1 from the surface of the toner particle, compared to ratio Y1 at the surface of the toner particle. In addition, for toners 1 and 2, the reduction rate of ratio Y was always 50% or more even at a depth of 10 nm to 30 nm from the toner particle surface. Furthermore, in the cases of toners 3 and 4, the rate of decrease in ratio Y was always 50% or more even at a depth of 20 nm to 30 nm from the toner particle surface.
[0083] (Production Examples of Developers 2 to 7) As shown in Table 2, developers 2 to 7 were obtained in the same manner as in the production example of developer 1 using each toner. Furthermore, these evaluations were carried out in the same manner as for Developer 1. The results of each evaluation are shown in Table 2.
[0084] [Table 2]
[0085] <Comparative Examples 1 to 2> (Toner 8 and 9 manufacturing examples) Toners 8 and 9 were obtained in the same manner as in the production example of toner 1, except that the binder resin type was changed as shown in Table 3 and the heat treatment conditions of the toner were changed so that the amount X1 and ratio Y of the silicone moiety were as shown in Table 3. The heat treatment conditions were changed as follows: For toners 8 and 9, the hot air temperature was set to 160° C., and the other heat treatment conditions were the same as those for toner 1.
[0086] [Table 3]
[0087] (Production examples of developers 8 and 9) As shown in Table 4, using each toner, in the same manner as in the production example of developer 1, developers 8 and 9 were obtained. Furthermore, these evaluations were carried out in the same manner as for Developer 1. The evaluation results are shown in Table 4. In Comparative Example 1, the rate of decrease in the amount of silicone moieties inside the toner relative to the toner surface was small, and the internal cohesive force of the toner decreased, resulting in a folding resistance of rank D. Since the polyester resin A having the structure represented by 1) was not used, the releasability was rated as D rank.
[0088] [Table 4]
Claims
1. A toner having toner particles containing a binder resin, The binder resin contains 50% by mass or more of a polyester resin, The polyester resin contains a polyester resin A having a structure represented by the following formula (1): In an analysis of the toner particles using an X-ray photoelectron spectrometer, the -(Si(R X ) 2 O) n -Si(R X ) 2 the ratio of the number of silicon atoms belonging to the silicone moiety represented by - to the total number of atoms measured (number of silicon atoms / total number of atoms×100) is defined as X, the value of X on the surface of the toner particle is defined as X1, and the value of X at a position 30 nm deep from the surface of the toner particle is defined as X2, In an analysis of the toner particles using an X-ray photoelectron spectrometer, when the ratio of the number of carbon atoms belonging to ester bonds of the polyester resin to the measured total number of atoms (number of carbon atoms / total number of atoms×100) is taken as Z, the value of Z on the surface of the toner particle is taken as Z1, and the value of Z at a position 30 nm deep from the surface of the toner particle is taken as Z2, X1 is 0.5 atomic % or more and 20.0 atomic % or less, A toner, wherein Y1 represented by the following formula (2) and Y2 represented by the following formula (3) satisfy the following formula (4). In formula (1), R X each independently represents a hydrogen atom, a methyl group, or a phenyl group; A represents a polyester moiety; B is a polyester moiety or -R 20 OH, -R 20 COOH, , and -R 20 N.H. 2 R represents any functional group selected from the group consisting of 20 represents a single bond or an alkylene group having 1 to 4 carbon atoms, The average number of repetitions n is 10-80. Y1=X1 / Z1 (2) Y2=X2 / Z2 (3) (Y1-Y2) / Y1≧0.50 (4)
2. 2. The toner according to claim 1, wherein the content of the polyester resin in the binder resin is 70% by mass or more.
3. 2. The toner according to claim 1, wherein the binder resin is a polyester resin.
4. When the value of X at a position 20 nm deep from the surface of the toner particle is X3 and the value of Z at a position 20 nm deep from the surface of the toner particle is Z3, Y3 expressed by X3 / Z3 and Y1 are expressed as follows: (Y1-Y3) / Y1≧0.50 4. The toner according to claim 1, which satisfies the above condition.
5. When the value of X at a position 10 nm deep from the surface of the toner particle is X4 and the value of Z at a position 10 nm deep from the surface of the toner particle is Z4, Y4 expressed by X4 / Z4 and the above-mentioned Y1 are expressed as follows: (Y1-Y4) / Y1≧0.50 5. The toner according to claim 1, which satisfies the above condition.
6. 6. The toner according to claim 1, wherein the toner particles contain a crystalline polyester resin.
7. The toner according to claim 6, wherein the content of the crystalline polyester resin is 0.5 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the binder resin.
8. 8. The toner according to claim 1, wherein X1 is from 7.0 atom % to 12.0 atom %.
9. The polyester resin A having the structure represented by the formula (1) has the silicone moiety and the polyester moiety, 9. The toner according to claim 1, wherein the polyester portion is an amorphous polyester resin.
Citation Information
Patent Citations
Electrophotographic toner composition and its production
JP1996087127A
Composite polyester resin
JP2002012657A
Resin for toner, toner, developer, and image forming apparatus
JP2012242448A
Toner for electrostatic charge image development
JP2013205579A
Toner and toner manufacturing method
JP2018017858A